If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3=(37/y)
We move all terms to the left:
3-((37/y))=0
Domain of the equation: y))!=0We add all the numbers together, and all the variables
y!=0/1
y!=0
y∈R
-((+37/y))+3=0
We multiply all the terms by the denominator
-((+37+3*y))=0
We calculate terms in parentheses: -((+37+3*y)), so:We get rid of parentheses
(+37+3*y)
We add all the numbers together, and all the variables
(3y+37)
We get rid of parentheses
3y+37
Back to the equation:
-(3y+37)
-3y-37=0
We move all terms containing y to the left, all other terms to the right
-3y=37
y=37/-3
y=-12+1/3
| 2c—-7=15 | | 162+2h=984 | | -7h-4=3-8h | | 1/21/2(6x-4)+4x=26 | | w^2+24w=3456 | | 5x+10(x+7)=145 | | 187+x=180 | | -4+2x=3+x | | 8b2+16b+19=5b2 | | 3b+9=10 | | 12=(8-x)x | | +4=5y+6 | | 3/c-3=1 | | -66+10x=4x+144 | | 5n-3(4n+1)=2n(4n+1) | | 3x^2-8x=-16 | | -10+p/2=-15 | | 5=3q-7 | | 12v=34 | | -3(4x+5)=0 | | 2x+3=-15-x | | 85+(6x+67)=180 | | -3h-(-12)-12h+(-10)= | | -y-4(2y+3)=15 | | 15=25+2x | | (2x+1)-4=56 | | 2(x+5)-2=24 | | -4b-6b=8-2b | | -x-15+9x=3x+2+4x | | 2(5x+1)-3x=3(2x+2) | | R/6+5r/6=2 | | 2-4=2s |